Receptor for Advanced Glycation End Products Acts as a Fuel to Colorectal Cancer Development - Azizian-Farsani, Fatemeh; Abedpoor, Navid; Hasan Sheikhha, Mohammad; Gure, Ali Osmay; Nasr-Esfahani, Mohammad Hossein; Ghaedi, Kamran (Frontiers in Oncology, 2020)
Receptor for advanced glycation end-products (RAGE) is a multiligand binding and single-pass transmembrane protein taken in diverse chronic inflammatory conditions. RAGE behaves as a pattern recognition receptor (PRR) which binds and is engaged in the cellular response to a variety of damage-associated molecular pattern molecules (DAMPs) as well as HMGB1, S100 proteins, AGEs (Advanced glycation end products). The RAGE activation turns out to an formation of numerous intracellular signaling mechanisms resulting in the progression and prolongation of colorectal carcinoma (CRC). The RAGE expression correlates well with the survival of colon cancer cells. RAGE involved in the tumourogenesis which increases and develops well in the stressed tumour microenvironment. In this review, we intend to summarize the current view of molecular mechanisms involved in the multi-ligand activation of RAGEs leading to the downstream signaling cascade activation particularly in the inflammatory tumor microenvironment in CRC. A better understanding of its contribution may provide new targets for tumor management and risk assessment.